Pre-concentration of Cd(II), Cr(III), Cu(II) and Ni(II) on a column packed with free carboxymethylcellulose (CMCH) - Padilha, Pedro de Magalhães [UNESP]; Rocha, Julio Cesar [UNESP]; Campos, Joaquim T.S. [UNESP]; Moreira, José Celso [UNESP]; Federici, Cilene C. [UNESP] (FapUNIFESP (SciELO), 1997)
Carboxymethylcellulose packed in to a glass column was used to pre-concentrate metallic cations from aqueous solutions. The pre-concentrated metal cations are directly eluted from the column using 5.0 mL of 1.0 mol L -1 hydrochloric acid. The optimum pre-concentration conditions are given (glass column, 16 cm length, 0.80 cm i.d., stationary phase height of 12 cm, flow-rate, 1.5 mL min -1). The recuperation efficiency achieved is greater than 95%, while the enrichment factor is 10 for 50 mL of solution (0.50 mg L -1 each).
Keywords: Adsorption; Carboxymethylcellulose; Pre-concentration